A zirconia-based wideband biological tissue identification probe with enhanced penetration depth - Wu, Guangmin; Liu, Zhongyi; Yang, Zitong; Mu, Delu; Xu, Hu; Sun, Jiahong; Ou, Zi; Tian, Yufeng; Chen, Xingye; Peng, Yanhua; Wang, Jiandong (Frontiers in Physics, 2026)
The development of non-invasive probes with significant penetration depth is crucial for quickly characterizing biological tissues during surgical resection specimens, ensuring the full removal of tumors. This paper presents a novel zirconia probe designed to transmit low-power transcutaneous signals for identifying subcutaneous tumors without damaging biological tissues. The probe features a high dielectric constant and combines zirconia with surface-coated copper layers that have a low dielectric constant. This design achieves ultra-wideband matching from 2.8 GHz to 15.1 GHz for biological tissues. Simulations and experimental measurements on ex vivo porcine skin, fat tissue, and muscle tissue placed above the probe allowed us to differentiate tissues using reflection coefficient analysis. The results showed a penetration depth of 19 mm, with biological safety confirmed through specific absorption rate (SAR) simulations. Tumor phantoms embedded within biological matrices demonstrated the probe’s ability to detect lesions larger than 5 mm in diameter. Finally, the potential of the probe for rapid clinical identification was verified through tumor detection and scanning imaging of clinical samples.